2003
DOI: 10.1063/1.1578174
|View full text |Cite
|
Sign up to set email alerts
|

Operational mechanism of light-emitting devices based on Ru(II) complexes: Evidence for electrochemical junction formation

Abstract: In this work, the operational mechanism of single-layer light-emitting electrochemical cells (LECs) based on the small molecule tris(2,2’ bipyridyl) ruthenium(II) [Ru(II)] was investigated using capacitance and resistance measurements. The current–voltage and capacitance–voltage characteristics of such devices suggest that an electrochemical junction is formed during operation with a high electric field across the junction. A similar mechanism has been proposed for polymer LECs. In the case of Ru(II) devices, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 32 publications
2
45
0
1
Order By: Relevance
“…First attempts were made using impedance spectroscopy, a technique that applies a small AC perturbation on a DC voltage to get information on the resistance and capacitance of the active material, and supported the ECD model. [57,58] In fact, the standard tools for studying conventional light-emitting devices, which entail the measurement of luminance (L) and current density (J) as a function of voltage (V) JL-V measurements, are difficult to use in LECs because the application of a voltage triggers the movement of ionic charges and physically modifies the device itself. Therefore, to obtain reliable operative parameters of a LEC for a given ionic distribution, it is crucial to avoid ionic movement during the JL-V scans.…”
Section: Lecs: Mechanism Of Workmentioning
confidence: 99%
“…First attempts were made using impedance spectroscopy, a technique that applies a small AC perturbation on a DC voltage to get information on the resistance and capacitance of the active material, and supported the ECD model. [57,58] In fact, the standard tools for studying conventional light-emitting devices, which entail the measurement of luminance (L) and current density (J) as a function of voltage (V) JL-V measurements, are difficult to use in LECs because the application of a voltage triggers the movement of ionic charges and physically modifies the device itself. Therefore, to obtain reliable operative parameters of a LEC for a given ionic distribution, it is crucial to avoid ionic movement during the JL-V scans.…”
Section: Lecs: Mechanism Of Workmentioning
confidence: 99%
“…42 Lately, van Reenen et al demonstrated a junction width to active layer thickness ratio of 0.3-0.8 dependent on the semiconducting polymer used. 48 In case of an iTMC-LEC comprising an iridium(III) complex similar to the one used in this work, Lenes et al recently highlighted a strong decrease in the effective thickness from 120 nm to 26 nm at a low operating voltage of 3.5 V. 38 In general, thinner junctions were observed at higher operating voltages 47,52 and for devices with higher ionic conductivity, respectively. 52 …”
Section: B Transient Behavior Of the Itmc-lec In Operationmentioning
confidence: 99%
“…It is to be noticed that the thickness of the intrinsic region was found to be strongly dependent on the operating voltage. 41,47,52 The transient impedance and phase angle of the iTMC-LEC as a function of frequency recorded at a bias voltage of 3 V are illustrated in Figure 2. Applying the bias to the device leads to a continuous decrease in the impedance with operating time (Figure 2(a)).…”
Section: B Transient Behavior Of the Itmc-lec In Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…[28,29] The p-n junction is built at a temperature at which the ions are mobile, and the device is thereafter cooled to a temperature at which the ions effectively become immobile and the p-n junction as a consequence is stabilized. [30][31][32][33][34][35][36] Lonergan and co-workers stabilized a p-n junction at the interface between a cationic and an anionic conjugated polyelectrolyte by solvent-induced removal of the mobile counter-ions, [37] while Bazan et al utilized in-situ boron-fluoride chemistry on a similar device structure for the same purpose. [38] Finally, Leger and Bartholomew [39] conceptualized the more generic "chemical stabilization" approach, which utilizes designed dopant counter-ions that can be physically immobilized via cross-linking polymerization reactions that presumably are initiated by electrochemical means.…”
Section: Introductionmentioning
confidence: 99%